THE INFLUENCE OF LOCAL WISDOM VALUES IN CIVIC EDUCATION LEARNING ON STUDENTS’ CIVIC RESPONSIBILITY IN THE PANCASILA AND CIVIC EDUCATION STUDY PROGRAM, FACULTY OF TEACHER TRAINING AND EDUCATION, PASUNDAN UNIVERSITY, BANDUNG - Indah Khoirunnisa Tosin; Jajang Hendar Hendrawan; Neneng Tripuspita (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
Higher education has a strategic role in forming a young generation that is not only intellectually smart but also has responsibility as citizens. However, a significant gap between civic knowledge and civic disposition exists, characterized by declining social participation and individualistic attitudes among students. This study aims to analyze the influence of Panca Waluya local wisdom values—comprising cageur (healthy), bageur (good), bener (true), pinter (smart), and singer (skilled)—integrated into Civic Education (PKn) learning on the civic responsibility of students at Universitas Pasundan. Employing a quantitative approach with an explanatory survey and associative method, data were collected from students in the Pancasila and Civic Education Study Program using a five-level Likert scale questionnaire. Analysis through simple linear regression via SPSS 27 indicates that the instrument is valid and reliable, and all parametric prerequisites, including normality, linearity, and multicollinearity, were satisfied. The results reveal a significant positive effect p < 0.05. The coefficient of determination of 0.758 demonstrates that local wisdom values contribute 75.8% to strengthening student civic responsibility. The research concludes that the internalization of Sundanese cultural philosophies, such as Silih-Asih, Silih-Asah, and Silih-Asuh, effectively transforms abstract Pancasila values into tangible social actions. This culture-based pedagogical model provides a vital framework for higher education institutions to develop graduates who are academically competent, ethically grounded, and deeply committed to addressing public interests..